Association between the proportionality of functional mitral regurgitation and survival after mitral valve operationCentral MessagePerspective - Makoto Mori, MD, PhD; Christina Waldron, BS; Sigurdur Ragnarsson, MD; Soh Hosoba, MD, PhD; Mina Zaky, MD; Dustin Lieu, MD; Markus Krane, MD; Arnar Geirsson, MD (JTCVS Open)
Objective: The concept of proportionate and disproportionate functional mitral regurgitation suggests that transcatheter edge-to-edge mitral repair may benefit patients with a smaller left ventricle relative to a higher regurgitant burden. The clinical relevance of proportionality remains unknown in mitral operations for ischemic mitral regurgitation. We aimed to characterize the association between mitral regurgitation proportionality and outcomes after mitral valve operations. Methods: By using the Cardiothoracic Surgery Trial Network's severe ischemic mitral regurgitation trial, we first identified the inflection point at which the risk of 2-year mortality changed along the spectrum of the mitral regurgitation proportionality (defined as effective regurgitant orifice area/left ventricular end-diastolic volume index) using a splined multivariable Cox proportional hazards model. Patients were dichotomized by the mitral regurgitation proportionality value. The Cox model evaluated the hazard of 2-year all-cause mortality between proportionate and disproportionate mitral regurgitation. Results: Among the 240 patients, the median age was 69 years (interquartile range, 62-75), and 38% (n = 90) were women. Patients with effective regurgitant orifice/left ventricular end-diastolic volume index proportion greater than 0.40 (more disproportionate mitral regurgitation) had a higher hazard of death compared with those with more proportionate mitral regurgitation. The 90-day and 1-year mortality were higher in patients with disproportionate mitral regurgitation (13% vs 6.2% for 90 days and 19% vs 12% for 1 year). In a multivariable Cox model, the disproportionate mitral regurgitation group had a statistically significantly higher hazard of death compared with the proportionate mitral regurgitation group (hazard ratio, 2.15, 95% CI, 1.16-3.98, P = .015). Conclusions: The clinical relevance of the proportionality of functional mitral regurgitation proposed in the transcatheter edge-to-edge mitral repair population may not generalize to surgical patient populations.